A comprehensive synthesis unveils the mysteries of phosphate‐solubilizing microbes. (21st July 2021) - Li, Jin‐tian; Lu, Jing‐li; Wang, Hong‐yu; Fang, Zhou; Wang, Xiao‐juan; Feng, Shi‐wei; Wang, Zhang; Yuan, Ting; Zhang, Sheng‐chang; Ou, Shu‐ning; Yang, Xiao‐dan; Wu, Zhuo‐hui; et al.
ABSTRACT: Phosphate‐solubilizing microbes (PSMs) drive the biogeochemical cycling of phosphorus (P) and hold promise for sustainable agriculture. However, their global distribution, overall diversity and application potential remain unknown. Here, we present the first synthesis of their biogeography, diversity and utility, employing data from 399 papers published between 1981 and 2017, the results of a nationwide field survey in China consisting of 367 soil samples, and a genetic analysis of 12986 genome‐sequenced prokaryotic strains. We show that at continental to global scales, the population density of PSMs in environmental samples is correlated with total P rather than pH. Remarkably, positive relationships exist between the population density of soil PSMs and available P, nitrate‐nitrogen and dissolved organic carbon in soil, reflecting functional couplings between PSMs and microbes driving biogeochemical cycles of nitrogen and carbon. More than 2704 strains affiliated with at least nine archaeal, 88 fungal and 336 bacterial species were reported as PSMs. Only 2.59% of these strains have been tested for their efficiencies in improving crop growth or yield under field conditions, providing evidence that PSMs are more likely to exert positive effects on wheat growing in alkaline P‐deficient soils. Our systematic genetic analysis reveals five promising PSM genera deserving much more attention.